2021
DOI: 10.1186/s12967-021-02713-9
|View full text |Cite
|
Sign up to set email alerts
|

Are there subgroups of chronic fatigue syndrome? An exploratory cluster analysis of biological markers

Abstract: Background Chronic fatigue syndrome (CFS) is defined according to subjective symptoms only, and several conflicting case definition exist. Previous research has discovered certain biological alterations. The aim of the present study was to explore possible subgroups based on biological markers within a widely defined cohort of adolescent CFS patients and investigate to what extent eventual subgroups are associated with other variables. Methods The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…98 Participants were asked 4 questions relating to pain intensity, and 7 questions pertaining to pain interference with general activity, with higher scores indicating greater pain severity and interference. Scores for the BPI pain severity and interference range from mild pain (1-3), moderate pain (4)(5)(6), to severe pain (7-10). 98,130 2.3.1.5.…”
Section: Brief Pain Inventorymentioning
confidence: 99%
See 1 more Smart Citation
“…98 Participants were asked 4 questions relating to pain intensity, and 7 questions pertaining to pain interference with general activity, with higher scores indicating greater pain severity and interference. Scores for the BPI pain severity and interference range from mild pain (1-3), moderate pain (4)(5)(6), to severe pain (7-10). 98,130 2.3.1.5.…”
Section: Brief Pain Inventorymentioning
confidence: 99%
“…Because of the complex nature and spectrum of symptoms in FMS and CFS, several studies have reported patient subgroups based on self-report measures, comorbidities, sociodemographic, physiological, and psychological variables using cluster analysis. 4,31,76,109 Investigating multiple symptom domains and profiling patient subgroups of similar phenotype may help identify disease severity, direct treatment allocation, and improve treatment efficacy. 105,119,124 Given the overlap in clinical features between these cohorts, existing knowledge on FMS and CFS may aid in the rehabilitation of patients suffering from post-COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…However, clustering was based on a limited number of symptoms or non-core (i.e. less frequently observed) symptoms [ 12 17 ], and/or a non-validated questionnaires was used to assess symptoms [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A thorough understanding of the biomarkers associated with post-stroke symptoms, could provide biological measurement processes for follow up or early diagnosis. Limited studies have undertaken molecular biomarker analysis for post-stroke fatigue, although several have been conducted on the molecular biomarkers associated with chronic fatigue syndrome [19][20][21]. Furthermore, several serum and salivary biomarkers have been identified in stroke survivors experiencing stress and depression [22,23].…”
Section: Introductionmentioning
confidence: 99%